An authentication strategy based on spatiotemporal chaos for software copyright protection. Issue 18 (6th August 2015) - Cao, Lvchen; Luo, Yuling; Bi, Jinjie; Qiu, Senhui; Lu, Zhenkun; Harkin, Jim; McDaid, Liam
Abstract: An authentication strategy is proposed in this paper for embedded system software copyright protection. It employs a chaotic coupled map lattices (CML) system to generate the pseudo‐random numbers, which are used to construct message authentication codes (MAC) for embedded system authentication. The CML has multiple lattices where the adjacent lattices have coupled effect. When the system initial condition (e.g. lattice values and system parameters) has a marginal change, the output will have a significant change. Therefore, the proposed scheme is highly secure as the final MAC is almost impossible to be compromised. The experiment is conducted on the platform of field programmable gate array, and its corresponding results demonstrate that the proposed strategy achieved a good security performance, a high computing speed and a relatively low area overhead. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The findings of this paper are as follows: a pseudo‐random number sequence generator design using the CML‐based chaos system, an authentication strategy and a workflow for the software copyright protection and a hardware implementation and a performance analysis of the embedded security module.